The Social Impact of Online Games on the Lives of Rural Communities in Deli Serdang Regency - Sitepu, Hosea; Fatmariza, Fatmariza; Moeis, Isnarmi; Erianjoni, Erianjoni (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
The habit of playing games has become a lifestyle that is favored by the community, especially the younger generation and even elementary school students in rural and urban areas. Especially in rural communities, the online game Higgs Domino Island is rife. The study aims to explore the factors of the rise of Higgs domino island online gambling and its impact on the community in the village of Kuta, Jurung, STM Hilir district, Deli Serdang regency. This type of research is qualitative research. This research is qualitative descriptive research with a case study method. In determining the informants researchers used a purposive sampling technique. The data was obtained through observation, interviews, and documentation for 3 months, starting from October 2022 until January 2023. The results showed that the factors causing the people of Kuta Jurung Village, STM Hilir District, Deli Serdang Regency to carry out online gambling, the Higgs domino island game, was due to a lack of awareness and concern from the community about the impact of gambling, besides that the majority of people also have low education and a background of socio-economic factors, situational, learning factors, perceptions of probability, and skills perception factors. The moral impact of Higgs domino island online game gambling includes unstable emotional levels, reduced social interaction, and increased criminal acts as evidenced by the increased theft of garden produce in the Kuta Jurung Village community.